解方程:2y-3[y-4(1-2y)-5]=10
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 18:05:07
解方程:2y-3[y-4(1-2y)-5]=10解方程:2y-3[y-4(1-2y)-5]=10解方程:2y-3[y-4(1-2y)-5]=102y-3[y-4(1-2y)-5]=102y-3[y-4
解方程:2y-3[y-4(1-2y)-5]=10
解方程:2y-3[y-4(1-2y)-5]=10
解方程:2y-3[y-4(1-2y)-5]=10
2y-3[y-4(1-2y)-5]=10
2y-3[y-4-8y-5]=10
2y-3y-12-24y-15=10
-25y-27=10
-25y=37
y=37/25
解括号
原式左侧=2y-3(y-4+8y-5)=2y-3(9y-9)=27-25y=10
所以y=17/25
解方程y-[3y-1]等于5【y+2]
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程:3y²-(2y+1)(y-2)=(y-5)(y+1)
解分式方程(y+3)/(y^2+y)-1/(1-y)=4/y要过程
4(2y+3)=8(1-y)-5(y-2)解方程
解方程:2y-3[y-4(1-2y)-5]=10
解方程3y+1/y+2+2/2-y=3-(3y/y的平方-4)
已知关于y的方程3分之2y-k-2分之y-k=y-1于方程3(y-2)=4y-5同解
(2y-3)(-y+4)=(y-2)(y-5)-3y(y-7/3)解方程
初一数学解方程:(y+4)/5-(y-5)=(y+3)/3-(y-2)/2
解方程:(y+4)/5+y+6=(y+8)/2-(y+4)/3要过程
-4y(y-1)=2-2y 解方程
y(5y-2)=6-4y 解方程
方程5y(2y-3)=(y+2)(y-2)-1
解方程3y(y-1)=2(1-y)
解方程3/y-1+5y-2/y2-y=6/y
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)